INVESTIGATING PERCEPTIONS OF UNDERGRADUATE SCIENCE EDUCATION STUDENTS ON THE USE OF ARTIFICIAL INTELLIGENCE (AI) IN THE TEACHING AND LEARNING OF MATHEMATICS (UNIZIK Journal of STM Education, 2025)
This   study investigated the perceptions of undergraduate science students regarding the use of artificial intelligence in the teaching of mathematics. The targeted population comprised  137 students( 42 male students and 95 female students)  in the school of  sciences,Nwafor Orizu College of Education, Nsugbe, Anambra State in 2024/2025 academic year .The  sample  represents the entire poulation of 137 students(comprises of   46 Biology ,18 Chemistry,10Mathematics ,4 Physics ,59 Computer Science) ,who enrolled for the Elementary Mathematics 1( MTH101)lesson using census sampling method  because  .This is becauseThe instrument for data collection was a 30 item 4 -point  scale questionnaire classified into five thematic category  named as Artificial Intelligence Perception Questionnaire(AIPQ). The data obtained was analyzed using mean, standard deviation and t-test statistics. From the findings  of the study, it was determined that artificial intelligence perceptions of the students of the Computer Science , Mathematics and Physics students perception were higher  than the students of the Biology and chemistry  departments. Also the negative perceptions of all sample groups about artificial intelligence concept are more significant than positive perceptions.Based on the findings,it was recommended among others that  the Nigeria curriculum should incorporate AI literacy, helping students understand the strengths, limitations, and proper applications of AI in mathematical problem-solving.
Keywords: Artificial Intelligence, Undergraduate Science Education Students, Perception, Teaching and Learning